2018
DOI: 10.1017/s1755048317000748
|View full text |Cite
|
Sign up to set email alerts
|

Strange Bedfellows? Attitudes toward Minority and Majority Religious Symbols in the Public Sphere

Abstract: In this study, we contend that distinguishing individuals who support bans on minority religious symbols from those who want to ban all religious symbols improves our understanding of the roots of opposition to minority religious symbols in the public sphere. We hypothesize that both groups are likely driven by markedly different motivations and that opposition to the presence of minority religious symbols in the public sphere may be the result of an alliance between "strange bedfellows", clusters of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…However, none have systematically explored the impact of holding liberal values, although O'Neill et al (2015) show the determinant role played by feminist arguments. Moreover, in a study of the sources of support for the Charter of Quebec Values (Bilodeau et al, 2018), we found that supporters of both the Charter and the removal of the crucifix from the National Assembly of Quebec were more liberal than those who opposed the Charter. In this article, we explore whether holding liberal values has distinct attitudinal consequences inside and outside Quebec.…”
Section: Notesmentioning
confidence: 91%
“…However, none have systematically explored the impact of holding liberal values, although O'Neill et al (2015) show the determinant role played by feminist arguments. Moreover, in a study of the sources of support for the Charter of Quebec Values (Bilodeau et al, 2018), we found that supporters of both the Charter and the removal of the crucifix from the National Assembly of Quebec were more liberal than those who opposed the Charter. In this article, we explore whether holding liberal values has distinct attitudinal consequences inside and outside Quebec.…”
Section: Notesmentioning
confidence: 91%
“…Research in the Netherlands has shown that those who object to what they consider unequal treatment of women and authoritarian childrearing practices among Muslim minorities do not necessarily show dislike or antipathy toward Muslims as a group (Hagendoorn & Poppe, 2012;Sniderman & Hagendoorn, 2007; see also . Similarly, a large-scale study in Canada found that a majority of people supporting the banning of religious symbols in the public sphere did not have anti-Muslim sentiments (Breton & Eady, 2015; see also Bilodeau, Turgeon, White, & Henderson, 2018). And among national samples in the UK, France, Germany, and the Netherlands, a substantial portion of people with a positive attitude toward Muslims supported a ban on headscarves (Van der Noll, 2010).…”
Section: Attitude Objectmentioning
confidence: 99%
“…Both Amnesty International and the Quebec Human Rights Commission condemned the Charter as in clear violation of existing human rights legislation. 2 The proposal launched a polarizing public debate that mixed concerns about gender equality and the religious repression of women with local expressions of republicanism, ethnic nationalism, anger about the marginalization of French within Canada, and global anxieties about the religious Other, particularly Muslims (Adelman, 2011;Bilodeau et al, 2018). Colleagues at the McGill Division of Social and Transcultural Psychiatry, concerned about the potential impact on the populations we serve, entered the debate with a letter to the newspapers and subsequent media interviews (Kirmayer et al, 2013).…”
Section: A Divisive Debatementioning
confidence: 99%